Bentuk Persiapan Perkawinan Keluarga Katolik di Stasi Betlehem Sekolaq Joleq - Yesepa; Wilfridus Samdirgawijaya; Fabianus Sidi (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2020)
The purpose of this study is to describe the form of coaching in the family and in the church experienced by married couples in the preparation of a Catholic family marriage. This study uses a qualitative descriptive type with the method of documentation, observation and interviews. Sources of data obtained from the study site, the results of the documentation by looking at evidence of a marriage certificate of a married couple. Observation by looking at the daily life of the family. Interview with a married couple. The results showed that the form of coaching in the family and in the church that was carried out, during childhood and adolescence, married couples almost never received an explanation of the differences between men and women, reproduction, dating and marriage. Only a few parents explain but not openly.